2012
DOI: 10.1111/sms.12036
|View full text |Cite
|
Sign up to set email alerts
|

Muscular adaptations after two different volumes of blood flow‐restricted training

Abstract: This study aimed to gain an insight into the adaptations of muscle strength and skeletal muscle thickness after two different volumes of blood flow restriction training (BFRT), and compare them with high-intensity training. The sample was divided into four groups: low-volume, low-intensity BFRT (BFRT LV); high-volume, low-intensity BFRT (BFRT HV); traditional high-intensity resistance training (HIT); and a control group, which maintained their routine activities (CON). Leg extension one repetition maximum (1RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 33 publications
9
92
0
8
Order By: Relevance
“…Although a high number of sets and repetitions have been used in LLRT Burd et al 2010bBurd et al , 2012Mitchell et al 2012;Abe et al 2012;Martin-Hernandez et al 2013;Wernbom et al 2013), Martín-Hernández et al (2013) recently showed that doubling the OC volume from four to eight sets resulted in no further benefit in muscle size or strength. The possibility of a volume threshold has been suggested in which additional volume provides no further benefits for both traditional resistance training (Gonzalez-Badillo et al 2006) and OC (Martin-Hernandez et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although a high number of sets and repetitions have been used in LLRT Burd et al 2010bBurd et al , 2012Mitchell et al 2012;Abe et al 2012;Martin-Hernandez et al 2013;Wernbom et al 2013), Martín-Hernández et al (2013) recently showed that doubling the OC volume from four to eight sets resulted in no further benefit in muscle size or strength. The possibility of a volume threshold has been suggested in which additional volume provides no further benefits for both traditional resistance training (Gonzalez-Badillo et al 2006) and OC (Martin-Hernandez et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…It has been evidenced that a single set (high-load) protocol stimulates myofibrillar protein synthesis (Burd et al 2010a), hypertrophy, and muscular strength (ACSM 2009). However, there is no available information concerning a lower threshold below the three sets of LI-BRF or NOC that could be enough to induce significant muscular adaptations (Martin-Hernandez et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…performing the protocol twice) had no additive effect on these adaptive responses [71]. This indicates that there may be a volume threshold over which further increases are not advantageous for muscular development.…”
Section: Training Volumementioning
confidence: 88%
“…We suggest that the proposed superiority in strength with periodized programs are often times explained by the principle of specificity. [28][29][30] For example, the studies that found linear periodization superior to a non-periodized program is likely due to the greater intensity (i.e. training at a higher % 1RM) performed at the end of the program which closely mimics the 1RM test that is used to assess strength (Table 1).…”
Section: Benefits For Muscular Strength?mentioning
confidence: 99%